Why not but I can't” – Influence of a ‘culture of poverty' on learning: A case study - Perera, M.E.S. (Paper presented at the 10 th Anniversary International symposium The issues and challenges of the 21 st century. 4 th -8 th July 2006 , Sabaragamuwa University of Sri Lanka ., 2008)
Culture of poverty could be defined as an entire way of life of the poor living in the vice and depression of life in all aspects of life. Lewis, (1970,p.85) states that “ in addition to being a condition of chronic economic poverty, the culture of poverty is characterized by the cognitive poverty of the ‘members’, instilling a fatalism with reference to any possibility of ever achieving a different way of life” Although. Education is one way in which such people could be empowered to develop a sense of self confidence and self worth children acquire the adult fatalism early and become learned helpless. This paper presents some of the findings of a study, which investigated the role of motivation as a contributing factor in second language learning in a disadvantaged school setting in Sri Lanka. In this ethnographic case study one of the key challenges that was identified was the “culture of poverty” and its influence on the teaching learning process of these students. This study was guided by two main research questions. The first asked how motivation to learn the second language contributed to its acquisition. Second, hoe motivation could be enhanced to promote possibilities of second language learning. These questions were examined in relation to a disadvantaged school setting, using a predominantly qualitative approach based on observational case studies. , The selected students been from diverse backgrounds permitted comparisons across the cases. These cases were analyzed using a combined theoretical framework based on an expanded version of the socio-educational model, attribution theory and learned helplessness theory. Based on this analysis an intervention programme was planned and implemented in the classroom. The findings of the study indicates that there is a correlation between motivation and language learning. Further, in spite of the adverse soci-economic backgrounds fro which the students come, their motivation to learn the second language can be enhanced. However, it is not the socio- economic and cultural background per se that affects motivation that the students make regarding their prior learning experiences. This a relationship between attributions and ‘cognitive poverty, was visible